2011
DOI: 10.1177/1545968311400092
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Coordinated Gait

Abstract: Improved gait coordination and function were produced by the multimodal Gait Training Protocol. FES-IM added significant gains that were maintained for 6 months after the completion of training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(49 citation statements)
references
References 27 publications
0
49
0
Order By: Relevance
“…Within that framework and those principles, the GCP integrates the use of strategies and tools into a cohesive protocol that can engage the motor learning principles to such an extent that coordination can be progressively improved to satisfy the goal of improving gait coordination. This protocol is the first gait coordination training method, to our knowledge, to synthesize and integrate gait training in such a manner and to be quantitatively tested [1]. In response to this GCP, the significant improvements in impairments and coordinated gait exhibited a high effect size and so were sufficiently robust to produce a statistically significant improvement in measures of functional activities and meaningful life role participation activities [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Within that framework and those principles, the GCP integrates the use of strategies and tools into a cohesive protocol that can engage the motor learning principles to such an extent that coordination can be progressively improved to satisfy the goal of improving gait coordination. This protocol is the first gait coordination training method, to our knowledge, to synthesize and integrate gait training in such a manner and to be quantitatively tested [1]. In response to this GCP, the significant improvements in impairments and coordinated gait exhibited a high effect size and so were sufficiently robust to produce a statistically significant improvement in measures of functional activities and meaningful life role participation activities [2].…”
Section: Discussionmentioning
confidence: 99%
“…The Gait Coordination Protocol (GCP) was successful in producing clinically and statistically significant gains in impairment, function, and life-role participation for those in the chronic phase after stroke who had exhibited persistent moderate to severe gait deficits [1][2][3]. The GCP was initially developed to test response to functional electrical stimulation (FES); notably, the GCP produced enhanced coordinated gait regardless of whether FES was used [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If systematically coordinated with RTT, perhaps FES's influence on spinal circuitry can be better controlled and enable patients to eventually walk without artificial assistance. At least one group, which has investigated the rehabilitative effect of combining FES with treadmill training, has suggested that FES not only strengthens muscles but might also activate sensory pathways in a way that improves coordination [56]. Our FES+RTT system is capable of timing the FES precisely with the robotcontrolled gait pattern in an attempt to reinforce such afferent feedback [48].…”
Section: Implications For Advancing Gait Rehabilitationmentioning
confidence: 99%